The role of cystatin-C and KIM-1 in chronic renal failure - Khotamova Raykhon Sulaymonovna (Miasto Przyszłości, 2023)
Chronic heart failure (CHF) is a disease in which the heart is unable to pump enough blood to supply the body with oxygen. It can occur as a result of many diseases of the cardiovascular system, among which the most common are coronary heart disease, hypertension, rheumatoid heart defects, and endocarditis.